The influence of attachment orientation on weight loss, eating behaviour and other health outcomes among patients undergoing bariatric surgery: A scoping review. (1st April 2020) - Douglas, Tanisha D.; Stephens, Jeffrey W.; Barry, Jonathan; Lee, Michelle D.; Wilkinson, Laura L.
Abstract: Attachment orientation is a psychological factor concerning our expectations of ourselves and others in interpersonal relationships. An emerging literature has suggested that attachment orientation may influence a range of outcomes associated with bariatric surgery. The purpose of this scoping review was to map the literature and examine the role of attachment orientation in the context of bariatric surgery. Studies conducted with patients who are undergoing or have undergone bariatric surgery, with a measure of attachment orientation and published by 21st July 2019, were located through electronic searches including Scopus, PubMed and Web of Science. 21180 studies were identified, of which 18 were retained for narrative synthesis. The major outcome themes reported were (1) post-surgery weight-loss/body mass index ( k  = 10), (2) eating behaviour ( k  = 9), (3) attachment orientation differences in bariatric surgery patients compared with control groups ( k  = 4) and 4) other mental and physical health outcomes ( k  = 12). Overall, the results showed that there was little evidence to suggest that poor attachment orientation is predictor of weight-loss following surgery. There was evidence to suggest that poorer attachment orientation relates to poorer eating behaviours both before and after surgery, that patients undergoing bariatric surgery are more likely to have a poorer attachment orientation and attachment orientation is related to mental health outcomes but not physical health outcomes for patients. However, where relationships were identified, there were considerable inconsistencies regarding the dimension of attachment orientation that drove the relationship. Future studies should consider appropriate sample sizes for studies, replication of key findings and longer durations for longitudinal studies.